How do Religiosity and Environmental Awareness influence Muslim Tourists’ Halal Culinary Repurchase Intention? - Patrisia, Dina; Abror, Abror; Engriani , Yunita; Aimon, Hasdi; Rahmiati, Rahmiati; Mulyani, Erly; Khuadthong, Bussalin; Aujirapongpan, Somnuk (International Review of Management and Marketing, 2026)
This study aims to investigate the extent to which religiosity, environmental awareness, attitude, resilience, and self-efficacy influence Muslim tourists’ intention to repurchase Halal cuisine. The data were obtained from a survey involving 500 Muslim travelers who had visited West Sumatra, Indonesia. Data were examined through the application of Partial Least Square Structural Equation Modeling (PLS-SEM). The findings indicate that Halal culinary repurchase intension has been influenced by self-efficacy and attitude significantly. Furthermore, religiosity emerged as a key determinant influencing environmental awareness, attitude, resilience and self-efficacy. Environmental awareness strongly affects individual resilience, which in turn serves as a precursor to attitude formation. The study also outlines certain limitations and offers directions for future research.